Shoulder Arthroplasty: State of the Art and Future Perspectives - Scheibel, Markus; Lädermann, Alexandre; Audigé, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focused on the advancements in the field of shoulder arthroplasty in recent years. These concern surgical indications that have dramatically evolved and planification and navigation. The rapid development of surgical techniques and new prosthetic designs, as well as glenoid and humeral reconstruction for various conditions, is also overviewed. Despite the important progress highlighted in this reprint, there is currently a myriad of prosthetic designs, highlighting the evolving nature of this field.